Primary Mechanism Study of Panax notoginseng Flower (Herb) on Myocardial Infarction in Rats. (2nd May 2019) - Zhou, Xin; Li, Zhi-Cheng; Chen, Pei-Pei; Xie, Rui-Fang
Abstract : Background . Panax notoginseng (Burk.) F. H. Chen is one of the most common herbs in China. Because of its good efficacy and little adverse reaction, Panax notoginseng has been used widely to treat cardiovascular diseases (CVDs). Objective . To investigate effects of Panax notoginseng flower (PN-F) on rats with myocardial infarction (MI). Methods . The proximal left anterior descending coronary artery in rats was ligated to induce acute myocardial infarction. Then, animals were randomly assigned to four experimental groups: MI control group, Betaloc control group (with Betaloc 10 mg/kg/d), FD500 (low-dose) group ( Panax notoginseng flower decoction 500 mg/kg, n = 10 ), and FD1000 (high-dose) group ( Panax notoginseng flower decoction 1000 mg/kg, n = 10 ). Panax notoginseng flower decoction or Betaloc was orally administrated for two to four weeks before and after operation. Sham-operated group was used as a normal untreated group, in which animals were treated with double distilled water, once daily. HE (hematoxylin and eosin) staining, immunofluorescent assay, TUNEL assay, quantitative real-time PCR, and western blot analysis were, respectively, performed to observe morphology, count mean minimal vessels, investigate apoptotic cells, and record gene (HIF-1, VEGFA, and KDR) and protein (Bcl-2 and Bax) expressions. Results . Two weeks after MI, PN-F significantly enhanced capillary density in the border area of MI, decreased infarct size, improved minimal vessels, suppressed cell apoptosis, and enhanced expressions of genes (HIF-1, VEGFA, and KDR) and proteins (Bcl-2 and Bax). Conclusions . PN-F demonstrated a potential herb to treat rats with myocardial infarction through promoting angiogenesis and inhibition of apoptosis in the infarct area.